PENERAPAN APLIKASI MENGHAFAL AYAT AL-QUR’AN JUZ 30 BERBASIS ANDROID - Muhammad Mukmin; Abdul Rasyid Sabirin; Sariudin Sariudin (JURNAL INFORMATIKA, 2022)
Utilization of information systems is needed to support the development and increase in interest in learning, one of which is interest in learning to memorize the Al-Qur'an. It is no longer difficult for us to learn the Koran because now to get information about the Koran itself, it is widely available in cyberspace. itself is widely available in cyberspace. The problem faced in memorizing the Qur'an is that it is rare to repeat the memorization of the Qur'an and often forget to remember the location of the memorized verses. The research objective is to make it easier to memorize the Al-Qur'an Juz 30 and this application is intended for every Muslim who has the will to memorize the Al-Qur'an. This research produces an application that can help memorize the Al-Qura'an juz 30 anywhere and anytime, by compiling verses of the Al-Qura'an, especially juz 30.